(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2018)
In this work I attempt a reformulation of Lewis’ Best System Account, explicitating the underlying formal conception of scientiﬁc theories and trying to deﬁne the concepts of simplicity, strength and balance. This essay is divided in three sections. In the ﬁrst one I introduce the Best System Account of natural laws and formulate the need for its improvement. In the second section I outline a formal framework where the notions of deductive system and scientiﬁc theory can be deﬁned precisely. In the last section the notions of simplicity, strength and balance are analyzed. To conclude I argue that the framework proposed does indeed provide the precision required. In addition, it also oﬀers interesting insights on the plurality of concepts of simplicity, strength and balance, and on the general enterprise of formalizing scientiﬁc theories.